Plant-Based Diets (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Consumer interest in plant-based diets has been rapidly increasing in the past decade. Non-dairy and non-meat alternatives have gone mainstream. New products are appearing in the marketplace continually. The marketplace has been driven recently by millennials and flexitarians. Food companies have focused on providing nutritious food products that satisfy the demand for alternative items that look and taste like their animal counterparts. The marketplace wants products that improve human and planetary health worldwide. Questions have arisen as to how nutritionally sound and healthy are these products. How sustainable are these plant-based diets? How significantly do they alter traditional dietary patterns? What impact do they have on food security? Do these plant-based meat and dairy alternatives help lessen environmental degradation? Are the new products considered ultra-processed foods? What are the barriers and motivations that drive people to switch to a plant-based diet? Will plant-based diets help in the goal to greatly diminish malnutrition and over-nutrition (leading to obesity) around the world? These questions challenge scientists to provide meaningful answers through their ongoing research. Some of these issues are discussed in this reprint, based upon the latest research.